The Core Content and Practical Approach of China’s Global Security Initiative - Jing, Lina; Ma, Yugang; Zhong, Yu (Pacific International Journal, 2023)
This research paper provides an overview of China’s Global Security Initiative, its essential components, and its practical implementation. Firstly, the paper highlights the significance of the Global Security Initiative in the broader context of China’s global security policy. It then outlines the core elements of the Global Security Initiative, which include promoting security cooperation, establishing a global security framework, and enhancing comprehensive security measures. Secondly, the author explores the practical approach of the Global Security Initiative, which emphasizes cooperation between states, international organizations, civil society, and the private sector. The author also describes the implementation of the Global Security Initiative, such as the establishment of the Global Security Initiative Working Group and its role in regional security cooperation. Furthermore, the author discusses how the Global Security Initiative fits into the Belt and Road Initiative. Lastly, the paper addresses the challenges posed by the Global Security Initiative, including the need for greater transparency and the establishment of an effective governance system. By offering insights into the Global Security Initiative and its implications for global security, the author provides valuable information on this topic. Overall, this paper provides a comprehensive overview of the Global Security Initiative, its core components, practical approach, implementation, and challenges, making it an informative read for anyone interested in China’s global security policy.